Effects of Glucagon-like Peptide-1 Receptor Agonists on Cardiac Function, Exercise Capacity and Quality of Life - Anastasia Shchendrygina; Amina Rakisheva; Ilya Giverts; Yasmin Rustamova; Anzhela Soloveva (Cardiac Failure Review)
Glucagon-like peptide-1 (GLP-1) receptor agonists (RAs) are emerging glucose-lowering agents primarily used in managing diabetes and obesity. Recently, GLP-1 RAs have garnered attention for their cardiovascular benefits beyond glycaemic control in patients with type 2 diabetes, exhibiting patterns previously seen in cardiovascular outcomes trials on sodium–glucose cotransporter 2 inhibitors, which now receive a high level of recommendation for the treatment of heart failure (HF). GLP-1 RAs have been increasingly investigated in HF cohorts, but mainly in small-scale studies reporting inconclusive findings regarding clinical outcomes and different safety profiles in HF patients with reduced and preserved ejection fractions. This review discusses the effects of GLP-1 RAs on surrogate HF outcomes, such as cardiac structure and function, exercise capacity and quality of life, in HF patients across the spectrum of left ventricular ejection fraction, to provide insights into the potential of these agents to be investigated in large clinical trials to evaluate clinical outcomes.